Application of Therapeutic Jurisprudence: A Different Approach to Punishment in Kenya - Kariuki, Eric (Strathmore Law Review, 2017)
A critical role of the State is the regulation of crime by maintaining law and order and, at the same time, punishing crime. This paper seeks to address the retrogressive way crime is punished in Kenya. The author proposes that this can be rectified through the application of the doctrines of therapeutic jurisprudence (TJ), a theory first propounded by David Wexler when he tried to create a solution to the treatment of mental health victims in criminal courts. This paper takes his theories and applies them to the Kenyan context. In addressing these issues, this paper shall first look at the existing theories behind punishment, with focus on incarceration as the primary form of punishment, and highlight their flaws. It shall then look at TJ and explain how it can be infused into the Kenyan legal system. In doing so, the paper argues, the effectiveness of punishment can be greatly increased.